TANGGUNG JAWAB PENGANGKUT ATAS KETERLAMBATAN PENUMPANG DAN BARANG MENGGUNAKAN ANGKUTAN UDARA DI INDONESIA - Muhammad Rifqi Sulthanbaghasana; Ardison Asri (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
Air transportation plays a crucial role in supporting the mobility of people and the distribution of goods, both nationally and internationally, especially in an archipelagic country like Indonesia. As public dependence on air transport increases, legal issues related to the carrier’s liability for delays in passenger and cargo transport frequently arise and lead to consumer dissatisfaction. This study focuses on two main problems: how the legal framework governing the transportation of passengers and goods in Indonesia is structured, and how airline liability is defined and implemented in cases of delay. The research adopts a normative juridical method using a statute approach, conceptual approach, and historical approach to examine existing regulations, relevant legal concepts, and the historical development of carrier liability in Indonesian aviation law. The findings indicate that the legal regulation of air transportation in Indonesia is comprehensively provided under Law Number 1 of 2009 on Aviation. However, in practice, its implementation still faces various challenges, particularly regarding delays, which are often handled in a non-transparent and unaccountable manner by airlines. Airlines are obligated to provide compensation for delays, but in reality, this often leads to disputes due to discrepancies between regulatory provisions and their execution. The study concludes that there is a strong need to strengthen monitoring mechanisms and legal protection for air transport service users to ensure legal certainty and improve the quality of service in Indonesia’s air transportation sector.